“Somos o lado da corda que arrebenta mais fácil”: repercussões da pandemia no trabalho de músicos ludovicenses - MACHADO, Brenda Barros (2022)
The arrival of the Covid-19 pandemic in Brazil, at the beginning of 2020, had a strong impact on the country's socio-economic situation with the unfolding of the health crisis. However, the chaos installed by the spread of the virus did not occur homogeneously, so there is no denying that the repercussions generated in the population widened their social differences, as well as the place of paramount importance that work occupies. Since the subjects inserted in the context of formal jobs suffered consequences, inevitably the informal workers, who already had weaknesses and financial insecurities inherent to their work format, were immensely harmed. Taking into account the artistic work as an informal line of work, in which the bonds are configured as eminently autonomous and without legal support, it is understood that these workers faced a context of great difficulties, since the measures of social isolation and suspension of events paralyzed the work of all the people involved. In addition, due to their informal, intermittent nature and easy virtual access, it is understood that artistic activities are more vulnerable to wage precariousness than formal jobs. Therefore, this study aimed to analyze the subjective repercussions in the work of musicians in the city of São Luís-MA in face of the context of the pandemic. It is worth mentioning that this research had the Psychodynamics of Work (PdT) as a theoretical reference, along with the reading of the Psychosociology of Work, considering that these approaches favor the understanding of the relationships that permeate the act of working, as well as the subjective factors involved. Based on Psychodynamics’ analytical categories, the specific objectives of this research were: to identify the experiences of pleasure-suffering in working with music; to know the meanings attributed to this work; and finally, to analyze the mediation strategies used by these workers since the beginning of the pandemic. A qualitative research was developed, with seven semi-structured interviews and a script prepared by the researcher. The results obtained were analyzed based on Critical Discourse Analysis (CDA), proposed by Fairclough, in order to corroborate the vision of a subject who is an actor in his own history, envisioning in language and discourse the way in which the social is manifested. The repercussions of the pandemic meant that the factors that already generated suffering, such as social devaluation, low remuneration and instability in presentations, only worsened during this period. Mediation strategies in the face of the impacts of the pandemic aimed to rationalize the circumstances experienced and seek compensatory means to alleviate the anguish. It was noticed that, even in the absence of work activities, there was a strengthening in the sense of work, due to the artist's rapprochement with his raw material (music), which acted as a source of pleasure and an escape valve from suffering. It was understood that the character of live work, as well as the recognition experienced by musicians can favor and enhance the experiences of pleasure, meaning and the resignification of suffering at work.